Towards a metamodern academic study of religion and a more religiously informed metamodernism - Clasquin-Johnson, Michel (HTS teologiese studies, 2017)
The academic study of religion has long enjoyed a variety of philosophies and methodologies. A new entrant to this list has now arisen: metamodernism. This article examines the claims of metamodernism and makes an initial attempt to relate it to the academic study of religion, both in its guise as Religious Studies and, more tentatively, as the Theological sciences. Metamodernism, with its emphasis on oscillation and simultaneity, shows great promise as an explanatory framework to understand certain current religious developments, such as the ‘Spiritual but not Religious’ phenomenon. It may also assist in creating a growing convergence between the various branches of the academic study of religion.